Is remaining indoors an effective way of reducing exposure to fine particulate matter during biomass burning events?. (4th May 2019) - Reisen, Fabienne; Powell, Jennifer C.; Dennekamp, Martine; Johnston, Fay H.; Wheeler, Amanda J.
ABSTRACT: Bushfires, prescribed burns, and residential wood burning are significant sources of fine particles (aerodynamic diameter <2.5 μm; PM2.5 ) affecting the health and well-being of many communities. Despite the lack of evidence, a common public health recommendation is to remain indoors, assuming that the home provides a protective barrier against ambient PM2.5 . The study aimed to assess to what extent houses provide protection against peak concentrations of outdoor PM2.5 and whether remaining indoors is an effective way of reducing exposure to PM2.5 . The effectiveness of this strategy was evaluated by conducting simultaneous week-long indoor and outdoor measurements of PM2.5 at 21 residences in regional areas of Victoria, Australia. During smoke plume events, remaining indoors protected residents from peak outdoor PM2.5 concentrations, but the level of protection was highly variable, ranging from 12% to 76%. Housing stock (e.g., age of the house) and ventilation (e.g., having windows/doors open or closed) played a significant role in the infiltration of outdoor PM2.5 indoors. The results also showed that leaving windows and doors closed once the smoke plume abates trapped PM2.5 indoors and increased indoor exposure to PM2.5 . Furthermore, for approximately 50% of households, indoor sources such as cooking activities, smoking, and burning candles or incense contributed significantly to indoor PM2.5 . Implications : Smoke from biomass burning sources can significantly impact on communities. Remaining indoors with windows and doors closed is a common recommendation by health authorities to minimize exposures to peak concentrations of fine particles during smoke plume events. Findings from this study have shown that the protection from fine particles in biomass burning smoke is highly variable among houses, with information on housing age and ventilation status providing an approximate assessment on the protection of a house. Leaving windows closed once a smoke plume abates traps particles indoors and increases exposures.